Synthesis of polyethersulfone/titanium dioxide membranes: analysis of morphology, mechanical properties, and water filtration performance - Mataram, Agung; Firdaus, Aneka; Yanis, Muhammad; Dani, Rahma; Nasir, Subriyer; Ismail, Ahmad Fauzi; Othman, Mohd Hafiz Dzarfan (Eastern-European Journal of Enterprise Technologies, 2024)
The increasing demand for clean water, driven by population growth, urbanization, and industrial activities, has led to significant challenges in public health, the economy, and the environment. Effective water purification technologies are essential to address this issue. This study explores using polyethersulfone (PES) polymer-based membranes reinforced with titanium dioxide (TiO2) nanoparticles for antifouling applications. The membranes were fabricated using an electric field treatment method. Scanning Electron Microscopy (SEM) revealed a pore size distribution between 1,170 μm and 7,122 μm, demonstrating that this method can be adjusted to create membranes with specific filtration characteristics. Atomic Force Microscope (AFM) analysis showed surface roughness between 150 and 500 nm, indicating that the membrane’s surface morphology can be customized to improve performance. Mechanical testing showed that the tensile strength of the membranes varied with the addition of TiO2: the pure PES membrane (TI0) had a tensile strength of 2.12 MPa, while the TI1 membrane (20 % PES, 1 % TiO2) exhibited a decrease to 1.84 MPa. The TI2 membrane (30 % PES, 1 % TiO2) showed an increase in tensile strength to 3.86 MPa, confirming the reinforcing effect of TiO2 on the membrane’s mechanical properties. Clean Water Permeability (CWP) testing indicated flux values of 2558.9 L/m2·h·bar for TI0, 1263.1 L/m2·h·bar for TI1, and 2763.9 L/m2·h·bar for TI2, highlighting the optimal balance of mechanical strength and permeability in TI2. The PES/TiO2 composite membrane, made using an electric field method, shows promise for water filtration due to its enhanced permeability, providing an efficient solution for water treatment